2015
DOI: 10.4103/1947-489x.210289
|View full text |Cite
|
Sign up to set email alerts
|

Experience with diabetic adolescents observing ramadan fasting

Abstract: Background and Aims: Fasting during the holy month of Ramadan is an obligatory duty for all healthy adult Muslims. Fasting can be a major challenge for adolescents with type 1 diabetes mellitus (T1DM) as they have to keep good glycemic control to avoid complications. Limited data was published regarding the safety of fasting Ramadan in adolescent patients with T1DM. We have therefore conducted this study addressing the question “Can adolescents with T1DM fast safely during the Holy month of Ramadan, without ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Overall, 69% of the total sample population completed the fasting, which is similar to smallbased population studies indicating that Ramadan fasting is a safe practice for children and adolescents with type 1 diabetes mellitus [4,8]. Of note, there was a significant gender difference with a female predominance in the two groups however data in this aspect showed diversities and all of which were of small size sample [2,9,10]. Nevertheless, Ramadan fasting is still considered a risk factor for developing acute complications such as diabetic ketoacidosis and hypoglycemia, particularly in conditions of unplanned fasting [10].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, 69% of the total sample population completed the fasting, which is similar to smallbased population studies indicating that Ramadan fasting is a safe practice for children and adolescents with type 1 diabetes mellitus [4,8]. Of note, there was a significant gender difference with a female predominance in the two groups however data in this aspect showed diversities and all of which were of small size sample [2,9,10]. Nevertheless, Ramadan fasting is still considered a risk factor for developing acute complications such as diabetic ketoacidosis and hypoglycemia, particularly in conditions of unplanned fasting [10].…”
Section: Discussionsupporting
confidence: 71%
“…Subsequently, pediatricians in several healthcare centers agree that adolescents may fast if they have good glycemic control, hypoglycemia symptom awareness, and frequent home glucose monitoring (GM) during the fast [2].…”
Section: Introductionmentioning
confidence: 99%
“…In many diabetes centers managing Muslim populations, healthcare professionals agree that adolescents can fast if they have reasonable glycemic control, good hypoglycemia awareness, and the willingness to frequently monitor their BGLs during fasting 33 . A recent survey indicated that almost 80% of physicians looking after children and adolescents with diabetes would allow them to fast if they wished 32 …”
Section: Should Adolescents With T1d Fast During Religious Observances?mentioning
confidence: 99%